Modelling the contaminant attenuation capacity of sandy soils in the vadose zone - Eigenhuis, Bernhard (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1997.